Nicaragua : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2017)
This Selected Issues paper analyzes Nicaragua's social security system, which is projected to run out of liquid reserves by 2019, several years earlier than anticipated. To avoid burdening the budget, reforms to the system are urgently needed. A deep actuarial, economic, and operational analysis is needed to design a comprehensive reform program. Such a program must ensure that the defined-benefit, pay-as-you-go system can sustain itself for another generation of workers and that improved health care benefits can be maintained. A politically acceptable, pragmatic solution appears within reach. However, the authorities should act quickly to avoid a costly bailout of the system.